2011
DOI: 10.1038/ijo.2011.83
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet-induced obesity on colitis-associated colon tumor formation in A/J mice

Abstract: Objective: Studies have indicated that obesity is associated with a higher risk of colorectal cancer. This study was performed to determine the effect of diet-induced obesity on the formation of azoxymethane (AOM)/dextran sodium sulfate (DSS)-induced colon tumors and to identify adiposity-related mechanisms. Methods: Male A/J mice were placed on either a high-fat diet (HFD; 45% of total calories from fat) or a normal diet (ND; 15% of calories from fat) for 12 weeks. To induce colon tumors, AOM was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 51 publications
1
23
1
Order By: Relevance
“…A study performed by Park et al found that HFD (45% kcal from fat)-induced obesity in male A/J mice facilitated tumor development (34). Contrary to this and consistent with our findings, Boddicker et al showed that a high-fat lard-based diet (60% kcal from fat) significantly decreased total colonic lesions compared with a LFD in male C57BL/6 mice (5).…”
Section: Discussioncontrasting
confidence: 57%
“…A study performed by Park et al found that HFD (45% kcal from fat)-induced obesity in male A/J mice facilitated tumor development (34). Contrary to this and consistent with our findings, Boddicker et al showed that a high-fat lard-based diet (60% kcal from fat) significantly decreased total colonic lesions compared with a LFD in male C57BL/6 mice (5).…”
Section: Discussioncontrasting
confidence: 57%
“…Excess accumulation of adipose tissue results in higher circulating concentrations of insulin, leptin, free fatty acids, and inflammatory cytokines that stimulate cancer cell mitogenesis, angiogenesis, and migration through receptor‐mediated intracellular signaling . In our previous study, elevated colonic expressions of IR and Ob‐R suggested the direct involvement of insulin and leptin in the development of colon tumor formation . Therefore, a strategy to prevent colorectal carcinogenesis might be to avoid excess amounts of circulating growth signaling molecules associated with adipose tissue.…”
Section: Discussionmentioning
confidence: 97%
“…Leptin is the critical regulator of intestinal inflammation [26] and a number of studies demonstrate that increases or decreases in the serum levels of leptin can, respectively, increase or decrease the AOM-induced and APC min⁡ models of intestinal tumorigenesis [27, 28]. Based on the literature, we propose that the lower white adipose tissue and lower circulating leptin levels may be responsible, in part, for the resistance to intestinal polyps formation observed in the two mouse models of intestinal cancer we previously tested.…”
Section: Discussionmentioning
confidence: 99%